Infant mortality during economic downturns and recovery - Mendoza, Ronald U (Archīum Ateneo, 2009)
This paper reviews the empirical literature on the impact of economic downturns on infant mortality. Drawing on this, it examines the possible impact of the presently unfolding global economic slowdown. While there is scope for further improving our understanding of the links between economic trends and infant mortality, the available empirical evidence does suggest that children face grave risks if the social impact of the global slowdown is unmitigated. There is also a risk that the global slowdown could undermine recent progress in reducing infant mortality. The analysis and evidence underscore several key areas for policy responses: a) providing humanitarian relief, including health and nutrition interventions to the most hard-hit and vulnerable groups; b) expanding social protection to the poorest and most vulnerable; and c) resuscitating growth in a way that is pro-poor and ensures that the recovery of household incomes - notably among the poor and low income households - is robust and sustained. The main message of this paper for policymakers is that, based on empirical evidence on past crises, the possible impact of the present crisis on infant mortality is nothing that cannot be mitigated by policies that protect children and women and ensure sufficient social investments in the first place.